(untitled) (Biodiversitas Journal of Biological Diversity, 2016)
The proboscis monkey (Nasalis larvatus) frequently visits certain lowland (baruh) and never visits other, although both lowlands are inundated during rainy season or even have no water during the dry season. Data on seedling, sapling, pole, and tree of two former lowlands and of two latter ones were collected. Important value indexes were compared based on Renkonen similarity index. Treatments on vegetation were qualitatively recorded. The former lowlands had more diverse vegetation and higher security level than the latter had. Food sources, such as Hevea brasiliensis, Syzygium stapfiana, Vitex pubescens, Elaeocarpus stipularis, and Artocarpus teysmanii were available and more abundant on the former lowlands which were poorly cared. However, such condition could change anytime, because all lowlands include in the cultivated area. Â© 2005 Jurusan Biologi FMIPA UNS Surakarta Keywords: lowland-edge vegetation, Nasalis larvatus, rubber forest, Tabalong.